The first female authors of the Journal of Urology. (August 2019) - Marchetti, Kathryn; Lee, Ted; Bloom, David A; Wan, Julian
Introduction: In 1917, Alma Hiller became the first woman to publish in the Journal of Urology ( JU ). Her contribution was followed by articles from Carol Beeler and Isabel Mary Wason. This study explores their careers and contributions. Methods: We reviewed JU articles from 1917 to 1925 and identified Hiller, Beeler, and Wason as the first three women authors. Using public records, we obtained information of their educations and careers. Results: Hiller demonstrated resilience in obtaining training and ultimately contributed to innovation in clinical chemistry. Beeler worked on research on metabolic physiology. Wason influenced both lab work and national policy. Conclusions: For female scientists entering the workforce in the late 1800s/early 1900s, reception was contingent upon the acceptance of male colleagues. Despite these barriers, Hiller, Beeler, and Wason contributed to novel discoveries. Their most influential contributions remain their historic presence as early female researchers and the first female authors in JU .